The Impact of Trading Activity on Volatility Transmission and Interdependence among Agricultural Commodity Markets: Phattanan Boonyanuphong, Songsak Sriboonchitta
This paper aims at studying the volatility and dependence structureamong the main agricultural commodity markets. It also investigates the impactof the trading activity of agricultural commodities and the ethanol listing on thevolatility transmission for the corn, soybean, and wheat markets. The C andDvine copula based GARCH model was used to explain the interdependence ofcorn, soybean, and wheat prices. We discovered that the listing of ethanol andthe trading activity had an impact on the price volatility of corn, soybean, andwheat. The results support the argument that the roles of nancialization and ofthe biofuel increase volatility in the agricultural commodity markets. Moreover,the dependencies between the corn and the wheat returns, and between the cornand the soybean returns have signicant variability over time and have highervariations of dependence with symmetrical tail dependences. The higher dynamicdependence and symmetric tail dependence indicate that opportunities to use therelated agricultural commodities for portfolio diversication are reduced, particu-larly during a downturn in the markets. , journal=Thai Journal of Mathematics, author=Team, Support, year=2014, month=Sep., pages=211–227